Response of the Bight of Benin (Gulf of Guinea, West Africa) coastline to anthropogenic and natural forcing, Part 2: Sources and patterns of sediment supply, sediment cells, and recent shoreline change. (1st February 2019) - Anthony, E.J.; Almar, R.; Besset, M.; Reyns, J.; Laibi, R.; Ranasinghe, R.; Abessolo Ondoa, G.; Vacchi, M.
Abstract: The Bight of Benin in the Gulf of Guinea, West Africa, forms an embayment between the Volta River delta in the west (Ghana) and the Niger River delta (Nigeria) in the east. The bight coast comprises sandy beaches backed by Holocene beach-ridge barriers. Incident swell waves, beachface gradient and the unidirectional longshore sand transport from west to east are intimately linked, generating a classic example of a strongly wave-dominated drift-aligned coast. The stability of this coast, which hosts several major cities in addition to three large international deepwater ports, has been strongly affected by human activities. We analyzed shoreline mobility and coastal area change over the period 1990–2015. Our results show how the stability of this coast has been strongly affected by the three ports therein, and by natural and human-altered shoreline dynamics related to the Volta River delta and to distributaries at the northwestern flank of the Niger delta. The combination of these factors has impacted alongshore sediment redistribution by segmenting the previously unrestrained longshore transport of sand that prevailed along this open coast. The result is a mixture of natural and artificial sediment cells increasingly dominated by shoreline stretches subject to erosion, endangering parts of the rapidly expanding port cities of Lomé (Togo), Cotonou (Benin) and Lagos (Nigeria), coastal roads and infrastructure, and numerous villages. Post-2000, the entire bight shoreline has undergone a significant decrease in accretion, which is here attributed to an overall diminution of sand supply via the longshore transport system. We attribute this diminution to the progressive depletion of sand-sized bedload supplied to the coast through the main Volta river channel downstream of the Akosombo dam, built between 1961 and 1965. Sand mining to cater for urban construction in Lomé, Cotonou and Lagos has also contributed locally to beach sediment budget depletion. Although alongshore sediment supply from the Volta River has been the dominant source of sand for the stability or progradation of the Bight of Benin coast, potential sand supply from the shoreface, and the future impacts of sea-level rise on this increasingly vulnerable coast are also important. The continued operation of the three ports and of existing river dams, and sea-level rise, will lead to sustained shoreline erosion along the Bight of Benin in the coming decades. Highlights: The wave-dominated Bight of Benin coast is subject to strong west-east longshore sand transport. The unidirectional longshore sediment transport system has been segmented by several ports. The resulting mix of natural and artificial sediment cells is associated with increasing shoreline erosion. This erosion threatens the coastal cities of Lomé, Cotonou and Lagos, and numerous villages. Lower sand supply from the dammed Volta River, ports, sea-level rise will maintain erosion.